Sport and Autism: What Do We Know so Far? A Review - Sidney Grosprêtre; Célia Ruffino; Cyrielle Derguy; Nicolas Gueugneau (SpringerOpen, 2024)
Abstract Autism, or autism spectrum disorders, is a neurodevelopmental condition characterized by limitations in social interaction, communication skills, and repetitive behaviors. Although motor disorders were previously considered marginal in autism, recent research has highlighted their significance. Numerous studies have underscored the positive impact of sports on autistic individuals. This article presents a comprehensive overview of the literature regarding the effects of sport interventions on autistic individuals and aims to extract general and practical recommendations. Initially, the article reviews the various characteristics of autism that are positively impacted by sports, ranging from psycho-social skills to motor behavior. Subsequently, it examines how different configurations of sports practice (individual/collective, indoor/outdoor, etc.) may be suitable for autistic individuals. Literature research was conducted in two databases, resulting in the inclusion of 92 articles meeting longitudinal criteria (i.e., containing full sport/physical activity programs with pre-to-post analyses) out of 1665 initially identified articles. The findings suggest that individuals with autism can benefit from sports across a wide range of physical, psychological, and social factors. Importantly, there is no full contraindication for any activity, although some may require specific step-by-step preparation. Each activity has the potential to provide benefits in specific areas, as discussed in the article. In conclusion, further research is needed to explore the most effective strategies for implementing sports programs and maximizing their benefits for individuals across the autism spectrum.